In search of safety : confronting inequality in women's imprisonment - Owen, Barbara A.; Wells, James, Ph.D.; Pollock, Joycelyn M., 1956- (Oakland, California : University of California Press, 2017)
In Search of Safety takes a close look at the sources of gendered violence and conflict in women's prisons. The authors examine how intersectional inequalities and cumulative disadvantages are at the root of prison conflict and violence and mirror the women's pathways to prison. Women must negotiate these inequities by developing forms of prison capital-social, human, cultural, emotional, and economic-to ensure their safety while inside. The authors also analyze how conflict and subsequent violence result from human-rights violations inside the prison that occur within the gendered context of.
Intersectional inequality and women's imprisonment -- Pathways and intersecting inequality -- Prison community, prison conditions, and gendered harm -- Searching for safety through prison capital -- Inequalities and contextual conflict -- Intersections of inequality with correctional staff -- Gendered human rights and the search for safety.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
eBooks on EBSCOhost
Keywords: Women prisoners -- United States -- Social conditions; Prisons -- Social aspects -- United States; Women prisoners -- Violence against -- United States; Women prisoners -- Abuse of -- United States; Prisonnières -- États-Unis -- Conditions sociales; Prisons -- Aspect social -- États-Unis.; Prisonnières -- Violence envers -- États-Unis.; SOCIAL SCIENCE -- Penology; SOCIAL SCIENCE -- Criminology; Prisons -- Social aspects; Women prisoners -- Social conditions; United States; american womens prisons; conflict in womens prisons; female inmates; female prisoners; gendered harm; gendered violence; human rights violations in prison; human rights; life in womens prison; physical safety in womens prisons; prison capital; prison conditions; prison conflict; prison life; prison persona; prison violence; prisoners rights; violence in womens prisons; womens pathway to prison; womens prisons in the us; womens prisons